A user programmed cohesive zone finite element for ANSYS Mechanical. (July 2017) - Lindgaard, E.; Bak, B.L.V.; Glud, J.A.; Sjølund, J.; Christensen, E.T.
Highlights: Cohesive zone finite element as a user programmable feature (UPF) in ANSYS Mechanical. Formulation includes mixed-mode cohesive law, adaptive integration, non-standard post-processing. Benchmarks prove UPF CZM element superior in terms of robustness and numerical efficiency. The effect of onset traction in the cohesive law depends severely on the initial crack length. Not recommended to lower onset traction for studies of short cracks and crack initiation. Abstract : Abstract: A cohesive finite element implemented as a user programmable feature (UPF) in ANSYS Mechanical is presented. Non-standard post-processing capabilities compared to current available cohesive elements in commercial finite element software packages have been defined and implemented. A description of the element formulation and the post-processing options are provided. Simulation studies are presented which serves to verify the implementation and compare the performance to ANSYS INTER205 cohesive element. The results show that the implemented element performs better in terms of ability to converge to a solution and requires fewer iterations to converge in the incremental Newton-Raphson solution procedure used. Additionally, a sensitivity study about the typical remedy to obtain convergent solutions having coarse meshes by lowering the onset traction is conducted. The study brings new insight to the effect of lowering the onset traction and recommendations of practical usage in case of coarse meshes are outlined.